Preliminary inventory of parasitoids associated with fruit flies in mangoes, guavas, cashew, pepper and wild fruit crops in Benin - Vayssières, Jean-François; Wharton, R.; Adandonon, A.; Sinzogan, A.A.C. (Springer, 2011)
Fruit flies are pests of great economic importance due to their quarantine pest status and losses recorded in West Africa. An inventory of parasitoids associated with fruit flies in mangoes, guavas, cashew, pepper and major wild fruit crops was carried out in northern-central Benin in 2005, 2006, and 2008. Tephritid parasitoids reared from field-collected fruits belonged to three families: Braconidae (97.2%), Eulophidae (1.6%) and Pteromalidae (1.2%). Fopius caudatus (Szépligeti) accounted for 73.8% of all the parasitoids and therefore was the most abundant and widely distributed parasitoid. The parasitism rate was 7.7%, with the highest recorded in wild fruit crop habitat. Ceratitis cosyra (Walker) (77%) was the fly host most commonly reared from fruits that produced F. caudatus. The recently introduced pest Bactrocera invadens Drew Tsuruta and White was rarely parasitized and only by Pachycrepoideusvindemmiae (Rondani) (Hymenoptera: Pteromalidae) at this time. This is the first report of the inventory of one native parasitoid species from B. invadens in Africa, especially in West Africa.